EXPLORING THE RELATIONSHIP BETWEEN SERVANT LEADERSHIP, SOCIAL RESPONSIBLE LEADERSHI , AND ORGANIZATIONAL COMMITMENT IN HOSPITALS - Muhammad Haykal; Nur Faliza; Marbawi; Khairawati (CV. Radja Publika, 2026)
This study aims to examine the relationship between Servant Leadership, Socially Responsible Leadership, and Organizational Leadership. Commitment among hospital employees. This study uses primary data obtained through questionnaires distributed to 119 employees. The data analysis technique used was Structural Equation. Modeling-Partial Least Squares (SEM-PLS) which includes validity, reliability, and hypothesis testing. The results of the study revealed that Servant Leadership has a positive and significant effect on Affective Commitment , Continuance Commitment , and Normative Commitment . Furthermore, Socially Responsible Leadership also has a positive and significant effect on the three dimensions of Organizational Commitment . These findings demonstrate the importance of leadership in shaping and enhancing employee loyalty, emotional attachment, and moral responsibility towards the hospital.